Discharge simulation in the sub-basins of the Amazon using ORCHIDEE forced by new datasets - Guimberteau, Matthieu (2012)
The aim of this study is to evaluate the ability of the ORCHIDEE land surface model to simulate streamflows over each sub-basin of the Amazon River basin. For this purpose, simulations are performed with a routing module including the influence of floodplains and swamps on river discharge and validated against on-site hydrological measurements collected within the HYBAM observatory over the 1980–2000 period. When forced by the NCC global meteorological dataset, the initial version of ORCHIDEE shows discrepancies with ORE HYBAM measurements with underestimation by 15 % of the annual mean streamflow at Obidos hydrological station. Consequently, several improvements are incrementally added to the initial simulation in order to reduce those discrepancies. First, values of NCC precipitation are substituted by ORE HYBAM daily in-situ rainfall observations from the meteorological services of Amazonian countries, interpolated over the basin. It highly improves the simulated streamflow over the northern and western parts of the basin, whereas streamflow over southern regions becomes overestimated, probably due to the extension of rainy spots that may be exaggerated by our interpolation method, or to an underestimation of simulated evapotranspiration when compared to flux tower measurements. Second, the initial map of maximal fractions of floodplains and swamps which largely underestimates floodplains areas over the main stem of the Amazon River and over the region of Llanos de Moxos in Bolivia, is substituted by a new one with a better agreement with different estimates over the basin. Simulated monthly water height is consequently better represented in ORCHIDEE when compared to Topex/Poseidon measurements over the main stem of the Amazon. Finally, a calibration of the time constant of the floodplain reservoir is performed to adjust the mean simulated seasonal peak flow at Obidos in agreement with the observations.